English Language Teacher’s Roles as Perceived by Senior High School Students - Rompas, Septianti Viranti; Sinadia, Alfrits Roul (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Klabat, 2025)
This research aimed to study the teacher’s roles played by English language teachersat a senior high school. It analyzed the levels of students’ perception of which teacher’s role isthe preferred one and which one is mostly played by their teachers. This study was conducted on 55 language major students at a public senior high school. To gather the data, it used questionnaires about different teacher’s roles in the classroom. It was a descriptivequantitative research which utilized statistical analyses to analyze the data. Based on theexisting findings, there are a few conclusions drawn. First, students show good preference for all types of teachers’ roles (controller, director, manager, facilitator, and resource). However, they show a very good preference for one type of role, that is as a facilitator. In other words, the English teachers who play their roles as facilitators would be the most preferred by the students in English learning. Second, since the English teachers at the school proportionally play all types of roles in their teaching activities, this indicates that the English teachers fully realize the importance of playing all types of roles when teaching rather than emphasizing only one or two types of roles.